Design av onboardingprocess för PR-ansvariga hos en ideell organisation - Gunnarsson, Isak; Hansson, Axel (My University, 2021)
The non-governmental organization Engineers Without Borders Sweden works with humanitarian engineering and consists of a national board and 13 local offices located all over Sweden. The local offices work, among other things, with engaging people and marketing the organization's various assignments and events. The organization has a problem, that their guidelines and templates for marketing is not always followed by the volunteers at the local offices. Based on this information, a study of the organization and what causes the instructions not being followed was made. The study was conducted in the form of questionnaires and interviews with volunteers at the local offices. An analysis of the information gathered showed that several different problems that affected the marketing existed. The analysis was the basis for a brainstorming process where different solutions were generated. Finally, the project resulted in a guide and process that will give new volunteers the conditions to easily understand and learn the work and thereby minimize the number of errors in marketing.